Self‐Limited Epitaxial Growth of Ultrathin Nonlayered CdS Flakes for High‐Performance Photodetectors - Jin, Bao; Huang, Pu; Zhang, Qi; Zhou, Xing; Zhang, Xiuwen; Li, Liang; Su, Jianwei; Li, Huiqiao; Zhai, Tianyou (Advanced functional materials, 2018)
2D nonlayered materials that possess appealing properties are entering the researchers' vision. However, direct access to the 2D level of these materials is still a great challenge due to the instrinsic isotropic chemical bond. This work presents the initially self‐limited epitaxial growth of ultrathin nonlayered CdS flakes (as thin as 6 nm) on mica substrate with a large domain size (>40 µm) by employing In2S3 as the passivation agent. Besides, the thickness and sizes of the products could be tunable by the addition level of In2S3 amount. The growth mechanism is evidenced via experiments and theoretical calculations, which is attributed to the surface distortion effect of In–S motif and the preference of local environments for In on the CdS (0001) surface. The photodetector designed on CdS flake demonstrates a high photoswitching ratio (up to 103), a high detectivity (D* ≈ 2.71 × 109 Jones), and fast photoresponse speed (τR = 14 ms, τD = 8 ms). The as‐proposed self‐limited epitaxial growth method opens a new avenue to synthetize 2D nonlayered materials and will promote their further applications in novel optoelectronic devices. This work presents the initially self‐limited epitaxial growth of ultrathin nonlayered CdS flakes (≈6 nm) on mica substrate with a large domain size (>40 µm) by employing In2S3 as the passivation agent. The growth mechanism is attributed to the surface distortion effect of In–S motif and the preference of local environments for In on the CdS (0001) surface.